2020
DOI: 10.1159/000510014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cellular Senescence on Dental Follicle Cells

Abstract: The dental follicle is part of the tooth germ, and isolated stem cells from this tissue (dental follicle cells; DFCs) are considered, for example, for regenerative medicine and immunotherapies. However somatic stem cells can also improve pharmaceutical research. Cell proliferation is limited by the induction of senescence, which, while reducing the therapeutic potential of DFCs for cell therapy, can also be used to study aging processes at the cellular level that can be used to test anti-aging pharmaceuticals.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Sox-2, Nanog1 and Nestin, are negative for hematopoietic stem cell markers such as CD11b, CD34, CD45 and HLA-DR [ 46 , 47 ]. Originating from the neural crest origin, hDFPCs can differentiate into osteoblasts, adipocytes, chondrocytes, cementoblasts and periodontal ligament cells as well as neuronal cells [ 47 , 48 ].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sox-2, Nanog1 and Nestin, are negative for hematopoietic stem cell markers such as CD11b, CD34, CD45 and HLA-DR [ 46 , 47 ]. Originating from the neural crest origin, hDFPCs can differentiate into osteoblasts, adipocytes, chondrocytes, cementoblasts and periodontal ligament cells as well as neuronal cells [ 47 , 48 ].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…hSCAPs are negative for CD14, CD34, CD45, CD150 and HLA-DR expression. These stem cells are also plastic adherent and clonogenic and express low levels of odontoblast markers such as dentin sialoprotein (DSP), matrix extracellular phosphoglycoprotein [ 48 ]. They also have multiple differentiation potentials and can be induced into osteo/odontoblasts, lipoblasts and neuroblasts in vitro [ 49 ].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Here, decreased cell proliferation is associated with induction of β-Galactosidase activity and increased cell size, which is typical for senescent cells. Interestingly, while preliminary data showed that dental stem cell markers such as CD105 did not change significantly after induction of cellular senescence, the differentiation potential in senescent DFCs decreased [ 110 , 111 ]. In general, senescent cells control the progression of the cell cycle in the G1 phase by inhibition of cyclin-dependent kinases (CDKs).…”
Section: Molecular Mechanisms Of the Osteogenic Differentiation Of Dfcsmentioning
confidence: 99%
“…Therefore, successful bone tissue engineering should involve a combination of abundant MSCs/ osteoprogenitor cells, a suitable mixture of biofactors to induce osteogenic differentiation, and scaffolds based on biomaterials. For dental tissue regeneration, the most eligible are MSCs derived from various dental sources, such as dental pulp-dental pulp stem cells (DPSCs) [13]; periodontal ligament-periodontal ligament stem cells (PDLSCs) [14,15]; gingiva-gingival mesenchymal stem cells (GMSCs) [16,17]; dental follicle or bilayered Hertwig's epithelial root sheath-dental follicle stem cells (DFSCs) [18]; subepithelial palatal soft tissue-palatal-derived stem cells (paldSCs) [19,20]; periapical cyst tissue-human periapical cyst mesenchymal stem cells (hPCy-MSCs) [21,22]; and stem cells from exfoliated deciduous teeth (SHED cells) and from human root apical papilla (SCAP) [23] (Table 1).…”
Section: Osteogenic Potential Of Dental Tissue-derived Mscsmentioning
confidence: 99%